2022
DOI: 10.1371/journal.pcbi.1010623
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic dynamics of Type-I interferon responses

Abstract: Interferon (IFN) activates the transcription of several hundred of IFN stimulated genes (ISGs) that constitute a highly effective antiviral defense program. Cell-to-cell variability in the induction of ISGs is well documented, but its source and effects are not completely understood. The molecular mechanisms behind this heterogeneity have been related to randomness in molecular events taking place during the JAK-STAT signaling pathway. Here, we study the sources of variability in the induction of the IFN-alpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 83 publications
2
15
0
Order By: Relevance
“…Stochastic events arise from ‘noise’, a term describing some randomness of molecular interactions in the cellular environment (Andrews et al, 2009 ). This model of stochastic origin of cell-to-cell variability was supported with experimental data (stimulation of Huh7.5 with IFNα) and mathematical modeling simulations conducted by Maier et al (Maier et al, 2022 ). Altogether, stochastic events are pivotal factors contributing to cell-to-cell variability during IFN-signaling.…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…Stochastic events arise from ‘noise’, a term describing some randomness of molecular interactions in the cellular environment (Andrews et al, 2009 ). This model of stochastic origin of cell-to-cell variability was supported with experimental data (stimulation of Huh7.5 with IFNα) and mathematical modeling simulations conducted by Maier et al (Maier et al, 2022 ). Altogether, stochastic events are pivotal factors contributing to cell-to-cell variability during IFN-signaling.…”
Section: Introductionsupporting
confidence: 64%
“…Importantly, when Rand et al (Rand et al, 2012 ) analyzed the induction of an antiviral state, the non-responder population was permissive to virus infection, while the responder population was protected. Similar follow-up studies supported a heterogonous response to IFNs, including to IFNβ (type I), IFNα (type I) and IFNλ3 (type III), in a variety of cell types (human airway epithelial cell line A549, hepatocyte-derived epithelial-like cell line Huh7.5, primary human hepatocytes, and murine intestinal epithelial cells) (Schmid et al, 2015b ; Bhushal et al, 2017a ; Maier et al, 2022 ; Bauhofer et al, 2012 ). Rand et al (Rand et al, 2012 ) developed a mathematical model and suggested that cell intrinsic stochasticity is responsible for a heterogeneous response to IFNβ in murine fibroblasts.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Each year, new models appear, describing systems that previously have not been dealt with. However, most efforts concentrate on pathways involved in determination of cell fate [64] , cell cycle [3] , response to stress [63] , [89] , carcinogenesis [125] , immune system responses [29] , [76] , or, most recently, micro-RNA-mediated regulation of intracellular processes [61] , [92] , [104] .…”
Section: Modeling Approaches and Methodsmentioning
confidence: 99%
“…Understanding the complex interplay between viruses and the innate immune response at the system level requires experimentation at the single-cell resolution combined with data-driven single-cell level computational modeling (Talemi & Höfer, 2018; Van Eyndhoven et al , 2021). Thus far, integration of quantitative data on Ifnb1 (IFNβ gene) and ISGs expression in single cells over time and stochastic modeling allowed to demonstrate that paracrine signaling has a major impact on heterogeneous cell responses to infection (Patil et al , 2015; Rand et al, 2012; Maier et al , 2022). Recently, benefits of interferon expression heterogeneity have been studied within a spatial agent-based model of an infection with a “generic” virus (Gregg et al , 2021).…”
Section: Introductionmentioning
confidence: 99%